The impact of systemic and copper pesticide applications on the phyllosphere microflora of tomatoes. (11th December 2014) - Ottesen, Andrea R; Gorham, Sasha; Pettengill, James B; Rideout, Steven; Evans, Peter; Brown, Eric
Abstract BACKGROUND Contamination of tomatoes by Salmonella can occur in agricultural settings. Little is currently understood about how agricultural inputs such as pesticide applications may impact epiphytic crop microflora and potentially play a role in contamination events. We examined the impact of two materials commonly used in Virginia tomato agriculture: acibenzolar‐S‐methyl (crop protectant) and copper oxychloride (pesticide) to identify the effects these materials may exert on baseline tomato microflora and on the incidence of three specific genera; Salmonella, Xanthomonas and Paenibacillus. RESULTS Approximately 186 441 16S rRNA gene and 39 381 18S rRNA gene sequences per independent replicate were used to analyze the impact of the pesticide applications on tomato microflora. An average of 3 346 677 (634 892 974 bases) shotgun sequences per replicate were used for metagenomic analyses. CONCLUSION A significant decrease in the presence of Gammaproteobacteria was observed between controls and copper‐treated plants, suggesting that copper is effective at suppressing growth of certain taxa in this class. A higher mean abundance of Salmonella and Paenibacillus in control samples compared to treatments may suggest that both systemic and copper applications diminish the presence of these genera in the phyllosphere; however, owing to the lack of statistical significance, this could also be due to other factors. The most distinctive separation of shared membership was observed in shotgun data between the two different sampling time‐points (not between treatments), potentially supporting the hypothesis that environmental pressures may exert more selective pressures on epiphytic microflora than do certain agricultural management practices. © 2014 The Authors. Journal of the Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.